Kompetensi Guru Profesional dan Penggunaan Aplikasi Quizizz di UPT SDN 13 Binamu Kabupaten Jeneponto - Y, Yulianti; Achruh, Andi; R, Rosdiana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe the professional competence of teachers and the use of the quizizz application in the learning process at UPT SDN 13 Binamu, Jeneponto Regency. This type of research uses qualitative research with descriptive methods. Data collection techniques are carried out through in-depth interviews. Informants in this study were teachers who teach at UPT SDN 13 Binamu. Data management techniques use data reduction, data display, data verification and to test the validity of the data using triangulation, namely source triangulation, time triangulation, and technique triangulation.  The results of the study indicate that the professional competence of teachers is generally in the fairly good category, marked by the ability of teachers to design learning, master the material, and carry out evaluations. However, there are variations in abilities between teachers, especially in adopting learning technology. The use of the quizizz application is still limited to some teachers who have better ICT skills. These teachers use quizizz as an interactive and fun evaluation media for students. While other teachers still face obstacles in the form of limited devices, internet networks, and lack of training. There is a positive relationship between the level of professional competence of teachers and the effectiveness of using quizizz. More competent teachers tend to be more innovative and adaptive to developments in educational technology.  The obstacles faced in using the quizizz application include limited facilities, internet access, and digital literacy of teachers. Therefore, continuous training and infrastructure support from the school and education office are needed.